A nonlinear piezoelectric energy harvester with magnetic oscillator - Tang, Lihua (2013)
This letter proposes a magnetic coupled piezoelectric energy harvester (PEH), in which the magnetic interaction is introduced by a magnetic oscillator. For comparison purpose, lumped parameter models are established for the conventional linear PEH, the nonlinear PEH with a fixed magnet, and the proposed PEH with a magnetic oscillator. Both experiment and simulation show the benefits from the dynamics of the magnetic oscillator. In the experiment, nearly 100% increase in the operating bandwidth and 41% increase in the magnitude of the power output are achieved at an excitation level of 2 m/s2.